Helical perylene diimide self-assembly with a redox-active molecular switch applied to humidity sensing. Issue 35 (26th August 2022) - Zhang, Li; Yang, Li; He, Yining; Han, Ji-Min
Abstract : A solution-processed supramolecular self-assembled helical nanofiber was prepared using viologen molecular switch-substituted perylene diimide (PDI-DV ) and was applied to active humidity sensing using water-controlled intramolecular charge transfer. Abstract : A helical humidity-resistive sensor was fabricated using the solution-processed supramolecular self-assembly of a viologen-substituted perylene diimide (PDI-DV ). The nanohelices obtained in iPr2 O/MeCN at −20 °C as well as the nanoribbons formed in iPrOH/MeCN at room temperature were fully characterized by UV-Vis spectroscopy, PXRD, TEM, SEM and AFM. DFT calculations and CV measurements indicated that through intramolecular charge transfer (ICT), the viologen served as a redox-active molecular switch triggered by water, which was further confirmed by transient absorption and fluorescence spectroscopy. Both nanohelices and nanoribbons showed great on/off ratios under 95% RH because the water molecules adsorbed on the nanostructure surface changed the energy level of the viologen, thus hindering the ICT. Due to the better contact of the PDI cores and the tinier scale, the current response of the nanohelices is an order of magnitude higher than that of the nanoribbons, which is further supported by specific surface area, pore size, and water vapor adsorption experiments. In humidity sensing tests, the helical morphology could give a higher response of ∼290 000, a proportional relationship over a wide range of humidity (23–100% RH), and fast response (21 s) and recovery time (29 s).